Analisis Porositas, Tekstur, dan Morfologi Karbon Tempurung Nipah Hasil Pirolisis Suhu Tinggi Untuk Anoda Baterai Sekunder - Theresia Evila Purwanti Sri Rahayu; Mohammad Nurhilal; Rosita Dwityaningsih (Infotekmesin, 2023)
Lithium-ion batteries are the recent main store of electrochemical energy that have been widely used for electronic equipment, electric vehicles, and also renewable energy storage such as wind and solar. Lithium-ion batteries have many electrochemical advantages but lithium availability in nature is reduced very quickly and its distribution is uneven throughout the world. Sodium is attractive as an alternative to lithium insertion for secondary batteries because of its abundant availability and oxidation reduction potential to standard hydrogen electrodes only 0.3 volts higher than lithium. This study aims to synthesize hard carbon from nipah shell biomass using thermal methods of low-temperature pyrolysis (lower than 200 oC) followed by high-temperature pyrolysis (higher than 1000 oC). Characterization is carried out by iodine number analysis to determine porosity and SEM-EDX to determine texture and morphology. The result of the analysis of carbon iodine number is 346.86 mg/g while SEM-EDX analysis showed that carbon has a structure similar to a combination of graphene and nano-tube carbon.